IMPLEMENTATION OF 4D BUILDING INFORMATION MODELING (BIM) USING TEKLA STRUCTURES - Kristnanda Floter Pardosi; Husnul Khatimi (CERUCUK, 2022)
Follow-on Project of the Tapin Regency Regional Secretariat Office Building located on Jalan Datu Suban, Tapin Utara, Kalimantan Selatan is a reinforced concrete building project that only applies manual scheduling which is present in the form of S Curve, PUPR Ministerial Regulation Number 9 of 2021 states that projects ought to be base on BIM. Therefore, this research will discuss implementing 4D BIM (scheduling) using Tekla on the Follow-on Project for the Construction of the Tapin Regency Regional Secretariat Office using Tekla to determine the use of BIM on scheduling obtained from contractors.This research method starts from studying the software and the object to be modeled, collecting the data such as as-build, S Curve, RAB. Data processing start from 3D modeling using Tekla Structures 2020, scheduling with Tekla Task Manager, and then 4D modeling with object representation.Scheduling made from the Budget Plan (RAB), S Curve, and interviews of related parties are then inputted into the Tekla Task Manager with dependencies which are applied into the bar chart. The 4D model is created using the visual logic with the integration of the 3D model created by scheduling, the development planning stages can be displayed according to the reviewed date. It was concluded that Tekla Structures could be applied in scheduling the follow-up project for the construction of the Tapin Regency Regional Secretariat Office Building.Keyword : scheduling, Tekla Structures, Tekla Task Manager, Model 4D, Follow-on Project.